Deciphering critical amino acid residues to modify and enhance the binding affinity of ankyrin scaffold specific to capsid protein of human immunodeficiency virus type 1 - Somphot Saoin (2018)
© 2018, Allergy and Immunology Society of Thailand. All rights reserved. Background: AnkGAG1D4 is an artificial ankyrin repeat protein which recognizes the capsid protein (CA) of the human immunodeficiency virus type 1 (HIV-1) and exhibits the intracellular antiviral activity on the viral assembly process. Improving the binding affinity of AnkGAG1D4 would potentially enhance the AnkGAG1D4-mediated antiviral activity. Objective: To augment the affinity of AnkGAG1D4 scaffold towards its CA target, through computational predictions and experimental designs. Method: Three dimensional structure of the binary complex formed by AnkGAG1D4 docked to the CA was used as a model for van der Waals (vdW) binding energy calculation. The results generated a simple guideline to select the amino acids for modifications. Following the predictions, modified AnkGAG1D4 proteins were produced and further evaluated for their CA-binding activity, using ELISA-modified method and bio-layer interferometry (BLI). Results: Tyrosine at position 56 (Y56) in AnkGAG1D4 was experimentally identified as the most critical residue for CA binding. Rational substitutions of this residue diminished the binding affinity. However, vdW calculation preconized to substitute serine for tyrosine at position 45. Remarkably, the affinity for the viral CA was significantly enhanced in AnkGAG1D4-S45Y mutant, with no alteration of the target specificity. Conclusions: The S-to-Y mutation at position 45, based on the prediction of interacting amino acids and on vdW binding energy calculation, resulted in a significant enhancement of the affinity of AnkGAG1D4 ankyrin for its CA target. AnkGAG1D4-S45Y mutant represented the starting point for further construction of variants with even higher affinity towards the viral CA, and higher therapeutic potential in the future.